Effect of the Roll Center Position on the Roll Damping of a Ship Section - Yildiz, Burak (CHAMBER MARINE ENGINEERS, 2018)
The accurate calculation of the viscous roll damping is important for the estimation of the ship roll motion. Viscous roll damping can be calculated experimentally or numerically using forced roll oscillation or free roll decay tests. Semi-empirical formulae derived from experiment data can also be used for the prediction of viscous roll damping. in this study, the effect of the roll center position on the roll damping of a ship midsection was investigated experimentally, numerically and by using Ikeda's semi-empirical method. The vertical position of the roll center were shifted from near-bottom to main deck level of the ship section. The roll damping coefficients were obtained experimentally and numerically (CFD) by applying forced oscillation tests to the ship midsection with bilge keels. Semi-empirical Ikeda method was also used for the comparison of the results. It was observed that the numerical results are in good agreement with experimental results and the estimation of roll damping with numerical method is better than Ikeda method.
Keywords: Viscous Roll Damping; Roll Center; Ikeda Method; CFD; Engineering; Transportation